2020
DOI: 10.34117/bjdv6n4-197
|View full text |Cite
|
Sign up to set email alerts
|

Uso de resíduos da região norte do estado de Santa Catarina na alimentação de bovinos sobre a saúde ruminal e hepática

Abstract: RESUMO O objetivo do trabalho foi avaliar os efeitos da utilização do engaço da banana (Musas pp) e do resíduo da pupunha (Bactrisgasipaes) sobre a saúde ruminal e hepática de bovinos. Para isso, foram realizados dois experimentos. No experimento I seis novilhas mestiças das raças Holandês e Jersey com idade entre 6 e 8 meses receberam 0,25% do peso vivo de matéria seca de engaço de banana na dieta. No experimento II sete vacas da raça Holandês, multíparas receberam 0,5% do peso vivo de matéria seca de resíduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been gaining prominence in the agricultural market, being that, the banana is one of the most produced and consumed fruits in the world (FAO, 2019). Casas et al (2020) concluded that the use of banana residues, in cattle, did not affect ruminal and hepatic health, being able to provide these animals. Banana peel has the potential to be used in sheep feed.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…It has been gaining prominence in the agricultural market, being that, the banana is one of the most produced and consumed fruits in the world (FAO, 2019). Casas et al (2020) concluded that the use of banana residues, in cattle, did not affect ruminal and hepatic health, being able to provide these animals. Banana peel has the potential to be used in sheep feed.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Banana crop residues have desirable physical-chemical characteristics (ALKARKHI et al, 2011), being taking advantage of various parts of the plant in the feeding of cattle with that observed by Souza et al (2016) and Casas et al (2020), nutritional value is considerable for ruminant feeding, residues "in natura" may present in its bromatological composition, crude protein values between 6.3 and 16.0%, ether extract of 2.2 10 the. 9%, carbohydrates of 26 the 46%; mineral matter de 6,4 the 12,9%, gross energy of 4,01 the 4,35 Mcal.kg -1 in DM (EMAGA et al, 2007;LEOBET, 2016), can be stored in the form of silage for use as bulky, and the obstacle to this form of conservation is the water content that may represent 92.3 a 78.6% of weight.…”
Section: Introductionmentioning
confidence: 99%